Productive Use of Natural Resources for Promotion of Horticultural Crop Production through Rooftop Rainwater Harvesting in Rain-Fed Hilly Areas of Punjab: Rooftop Rainwater Harvesting in Rain-Fed Hilly Areas - Hussain, Abid; Majeed, Sidra; Z. Khan, Muhammad; Farooq, Waqas (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Rainfall variability often results in low crop and fruit productivity in rain-fed hilly areas. Rooftop Rainwater Harvesting (RTWH) Technology can play a promising role in achieving agricultural production potential in these areas. Its adoption makes the supply of water sustainable for vegetables, fruit, and crop farming as well as domestic use. According to key informants, RTWH is being adopted in the study area on technical lines since the early 1990s. However, the availability of literature about economic aspects of the technology in the context of Pakistan is quite limited. This study is an effort to document the economic aspects of the technology including cost structure, potential benefits, net returns, and returns on investment. Thus, the study is based on a purposively selected sample of thirty farmers from Kotli Sattian and Murree tehsils of Rawalpindi district having operational RTWH systems installed at farms. The data have been analyzed for descriptive statistics and financial evaluation. Moreover, technical discussions with key informants and a detailed review of literature have also been made to substantiate the findings of the study. In the study area, farming families have diversified income sources with a considerably low share of agriculture in family income (19.5%). The mean command area of the RTWH systems at sample farms was 0.33 acres, which is allocated to different vegetables, and mainly to guava & citrus orchards. Benefit-cost ratios of vegetables and fruit farming through RTWH is 1.16, with returns on investment of 15 %, and a rate of return to labour of 0.95 in the first year of installation. Thus, technology is economically viable in the study area. Moreover, the financial gains of RTWH can be improved by enhancing storage capacity and increasing the command area.